Biodiversity of genes encoding anti-microbial traits within plant associated microbes - Mousa, Walaa K.; Raizada, Manish N. (Frontiers in Plant Science, 2015)
The plant is an attractive versatile home for diverse associated microbes. A subset of these microbes produce a diversity of anti-microbial natural products including polyketides, non-ribosomal peptides, terpenoids, heterocylic nitrogenous compounds, volatile compounds, bacteriocins and lytic enzymes. In recent years, detailed molecular analysis has led to a better understanding of the underlying genetic mechanisms. New genomic and bioinformatic tools have permitted comparisons of orthologous genes between species, leading to predictions of the associated evolutionary mechanisms responsible for diversification at the genetic and corresponding biochemical levels. The purpose of this review is to describe the biodiversity of biosynthetic genes of plant-associated bacteria and fungi that encode selected examples of antimicrobial natural products. For each compound, the target pathogen and biochemical mode of action are described, in order to draw attention to the complexity of these phenomena. We review recent information of the underlying molecular diversity and draw lessons through comparative genomic analysis of the orthologous genes. We conclude by discussing emerging themes and gaps, discuss the metabolic pathways in the context of the phylogeny and ecology of their microbial hosts, and discuss potential evolutionary mechanisms that led to the diversification of biosynthetic gene clusters.